Rekontruksi Tahap Awal Pembentukan Alam Semesta Dalam Tafsir Ilmi Zaglul Al-Najjar: Rekontruksi Tahap Awal Pembentukan Alam Semesta Dalam Tafsir Ilmi Zaglul Al-Najjar - Muliya Agustinawati; Yenni Rahman; Elizal Anwar (Ikhtisar: Jurnal Pengetahuan Islam, 2026)
This research is motivated by differences of opinion about the process of the formation of the universe, scientists and commentators have different opinions about the meaning of the union of heaven and earth, and the process of separation between the two and by what they are separated. This research aims to reconstruct the initial stages of the formation of the universe according to the scientific interpretation (tafsir ilmi) of Zaghlul Al-Najjar on the verse of QS. Al-Anbiya' verse 30. This research uses a qualitative method, because it aims to understand or study Zaglul Al-Najjar's interpretation of the origin of the universe with a library research approach. The interpretation method used is the tahlili interpretation method, because this research studies the interpretation of QS. Al-Anbiya' verse 30 in detail based on Zaghlul Al-Najjar's thoughts with a scientific approach, namely an approach that studies kauniyah verses through the lens of modern science.  Furthermore, the data analysis technique used in this ariticle is descriptive-analytical, namely by describing, elaborating, and analyzing the interpretation of relevant Quranic verses, then linking them to modern scientific findings. The results of the study indicate that Zaghlul Al-Najjar reconstructs the formation of the universe into two main stages: The first stage of the universe's creation began with a primary mass (something unified and integrated) which in Arabic is called "ratq." The second stage, the separation or destruction of this primary mass by Allah's command, is called "fatq".